Evaluation of Cognitive Behavioral Therapy on Improving Pain, Fear Avoidance, and Self-Efficacy in Patients with Chronic Low Back Pain: A Systematic Review and Meta-Analysis. (19th March 2022) - Yang, Jiajia; Lo, Wai Leung Ambrose; Zheng, Fuming; Cheng, Xue; Yu, Qiuhua; Wang, Chuhuai
Abstract : Background . Cognitive-behavioral therapy (CBT) is commonly adopted in pain management programs for patients with chronic low back pain (CLBP). However, the benefits of CBT are still unclear. Objectives . This review investigated the effectiveness of CBT on pain, disability, fear avoidance, and self-efficacy in patients with CLBP. Methods . Databases including PubMed, EMBASE, Web of Science, Cochrane Library, and PsycINFO were searched. RCTs examining the effects of CBT in adults with CLBP were included. The data about the outcome of pain, disability, fear avoidance, and self-efficacy were retained. Subgroup analysis about the effects of CBT on posttreatment was conducted according to CBT versus control groups (waiting list/usual care, active therapy) and concurrent CBT versus CBT alone. A random-effects model was used, and statistical heterogeneity was explored. Results . 22 articles were included. The results indicated that CBT was superior to other therapies in improving disability (SMD −0.44, 95% CI −0.71 to −0.17, P < 0.05 ), pain (SMD −0.32, 95% CI −0.57 to −0.06, P < 0.05 ), fear avoidance (SMD −1.24, 95% CI −2.25 to −0.23, P < 0.05 ), and self-efficacy (SMD 0.27, 95% CI 0.15 to 0.40, P < 0.05 ) after intervention. No different effect was observed between CBT and other therapies in all the follow-up terms. Subgroup analysis suggested that CBT in conjunction with other interventions was in favor of other interventions alone to reduce pain and disability (P < 0.05 ). Conclusion . CBT is beneficial in patients with CLBP for improving pain, disability, fear avoidance, and self-efficacy in CLBP patients. Further study is recommended to investigate the long-term benefits of CBT. This meta-analysis is registered with Prospero (registration number CRD42021224837).